Reliability Optimization Design of Two-stage Planetary Gear Wheel Hub Reducer based on MATLAB - Ke Fengqin; Tang Shixing (Jixie chuandong)
The low speed and high torque of the electric drive wheel truck requires a relatively large transmission ratio gear reducer,so the planetary gear wheel hub reducer system is widely used in such truck. According to the structural characteristics of the two-stage planetary gear wheel hub reducer,the traditional design method is used to analyze the reliability of the planetary gear system,and the parameters of the gear system are optimized according to the calculated reliability. The system maximum reliability is changed into the gear reliability maximum as multiple objective functions. Based on the actual conditions,the constraints are established. By using the MATLAB,the multi-objective optimization function is solved,the optimal parameters of the gear are obtained. Based on the optimal parameters of the planetary gear system,the reliability of the whole system is analyzed. The analysis results show that,after the optimized design,transfer efficiency is 0. 969,and the transfer ratio is 30. 54,which meet the requirements. The sun gear tooth surface contact strength reliability coefficient is 2. 52,and the second stage ring gear tooth root bending fatigue strength reliability coefficient is2. 59,and the second stage gear reliability is 0. 989,so the reliability is obviously improved. The safety level of coefficient parts is high. The service life of the system can meet the design requirements,which provide reference for the optimization design of the similar planetary gear system.